Hedge fund activism in Japan the limits of shareholder primacy - Buchanan, John 1951-; Chai, Dominic Heesang; Deakin, S. F. (Simon F.). (Cambridge Cambridge University Press, 2012)
Hedge fund activism is an expression of shareholder primacy, an idea that has come to dominate discussion of corporate governance theory and practice worldwide over the past two decades. This book provides a thorough examination of public and often confrontational hedge fund activism in Japan in the period between 2001 and the full onset of the global financial crisis in 2008. In Japan this shareholder-centric conception of the company espoused by activist hedge funds clashed with the alternative Japanese conception of the company as an enduring organisation or a 'community'. By analysing this clash, the book derives a fresh view of the practices underpinning corporate governance in Japan and offers suggestions regarding the validity of the shareholder primacy ideas currently at the heart of US and UK beliefs about the purpose of the firm"
Machine generated contents note: List of figures; List of tables; Acknowledgements; Note on transcriptions of Japanese names; 1. Introduction: hedge fund activism, Japanese corporate governance, and the nature of the company; 2. Companies, company law, and corporate governance; 3. The rise of shareholder primacy in America and Britain; 4. The emergence of activist hedge funds; 5. Firm-centric corporate governance: the evolution of the Japanese model; 6. Japan's unexpected credentials as a target for hedge fund activism; 7. The anatomy of hedge fund activism: funds, targets and outcomes; 8. Two turning points: Bull-Dog Sauce and J-Power; 9. Responding to activism: managers, investors, officials and the media; 10. 'Quiet activism': the future for shareholder engagement in Japan?; 11. Conclusion: after shareholder primacy; Methodological appendix; Bibliography.
Includes bibliographical references and index.
Keywords: Corporations -- Investor relations -- Japan; Stockholders -- Japan; Hedge funds -- Japan; Corporate governance -- Japan; BUSINESS & ECONOMICS / Management